2014
DOI: 10.1111/aos.12535
|View full text |Cite
|
Sign up to set email alerts
|

Lutein supplementation leads to decreased soluble complement membrane attack complex sC5b‐9 plasma levels

Abstract: ABSTRACT.Purpose: The purpose of this study was to investigate the effect of lutein on systemic complement activation in elderly individuals. Methods: Seventy patients with signs of early age-related macular degeneration (AMD) were included in this study. All subjects were randomly assigned to receive a 10 mg daily dose of lutein or a placebo for a time period of 1 year. EDTA blood was collected before and at various time-points during the study (0, 4, 8 and 12 months). The plasma level of the soluble compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…1 Macular pigment's anatomic location, 2 short-wavelength (blue) light filtering properties, 3 and antioxidant [4][5][6] and anti-inflammatory properties [7][8][9][10] make this pigment important for vision in diseased [11][12][13] and nondiseased retinas. 14,15 Given the importance of MP for vision and its role in reducing risk of age-related macular degeneration (AMD) progression, 16 there is clearly a need to measure this pigment accurately in vivo in the clinical and the research setting.…”
Section: Acular Pigment (Mp) Is Composed Of the Carotenoids Lutein mentioning
confidence: 99%
“…1 Macular pigment's anatomic location, 2 short-wavelength (blue) light filtering properties, 3 and antioxidant [4][5][6] and anti-inflammatory properties [7][8][9][10] make this pigment important for vision in diseased [11][12][13] and nondiseased retinas. 14,15 Given the importance of MP for vision and its role in reducing risk of age-related macular degeneration (AMD) progression, 16 there is clearly a need to measure this pigment accurately in vivo in the clinical and the research setting.…”
Section: Acular Pigment (Mp) Is Composed Of the Carotenoids Lutein mentioning
confidence: 99%
“…In view of the central role of FD in the C3 feedback loop and its raised levels in AMD, it has been suggested that it is one of the complement proteins that could be therapeutically targeted in AMD patients [76]. We have recently shown that lutein supplementation was able to markedly decrease the levels of plasma FD and the activation products C3d, C5a and sC5b-9 in patients with early AMD [77,78]. Earlier studies reporting FD levels in the plasma from AMD patients did not mention if their subjects were taking supplements.…”
Section: Complement Factor Dmentioning
confidence: 99%
“…Epidemiological studies have shown that a higher intake of zinc and lutein delays the progression of late AMD [76,82]. Not only lutein affects complement [77,78]. A Dutch study recently showed that zinc supplementation leads to decreased systemic complement activation in AMD [83].…”
Section: Amd: a Disease Caused By A Hyperactive Complement Systemmentioning
confidence: 99%
“…2,3 Macular pigment filters short-wavelength (blue) light and its constituent carotenoids have antioxidant 4,5 and anti-inflammatory properties. [6][7][8][9] Macular pigment's unique anatomic location, blue light filtering properties, and antioxidant and anti-inflammatory properties make this pigment important for visual function. 10 Macular pigment (and its constituent carotenoids) may have an important role in age-related macular degeneration (AMD) by reducing oxidative stress via its antioxidant properties as well as limiting the effect of inflammatory mediators in the pathogenesis of this condition.…”
mentioning
confidence: 99%